The Effect of ASEAN’s Digital Economy Growth on China’s Export Trade - Zhao, Li; Li, Lanxin (International Journal of Social Sciences and Public Administration, 2024)
Currently, the digital economy is emerging as a powerful catalyst for nations globally to enhance the caliber of their economies and to foster international trade. As one of China’s key trading partners, ASEAN holds immense potential in the growth of its digital economy, which is contributing positively to the trade interactions between China and ASEAN. Utilizing an expanded gravity model, this study investigates the influence of the digital economic progress in ASEAN countries on China’s export trade, drawing on panel data from China’s export activities with ASEAN member states between 2010 and 2022. The study shows that the degree of digital economic advancement among ASEAN member countries is diverse, with a general tendency towards improvement. The growth of the digital economy in these countries has a considerable impact on increasing the volume of China’s export trade to ASEAN. And the GDP, population, and trade and transport infrastructure of ASEAN member countries significantly contribute to the enhancement of China’s export trade.